SLC7A8 coding for LAT2 is associated with early disease progression in osteosarcoma and transports doxorubicin - Hurkmans, Evelien G. E.; Koenderink, Jan B.; van den Heuvel, Jeroen J. M. W.; Versleijen-Jonkers, Yvonne M. H.; Hillebrandt-Roeffen, Melissa H. S.; Groothuismink, Johanne M.; Vos, Hanneke I.; van der Graaf, Winette T. A.; Flucke, Uta; Muradjan, Grigor; Schreuder, Hendrik W. B.; Hagleitner, Melanie M.; et al. (Frontiers in Pharmacology, 2022)
Background: Despite (neo)adjuvant chemotherapy with cisplatin, doxorubicin and methotrexate, some patients with primary osteosarcoma progress during first-line systemic treatment and have a poor prognosis. In this study, we investigated whether patients with early disease progression (EDP), are characterized by a distinctive pharmacogenetic profile. Methods and Findings: Germline DNA from 287 Dutch high-grade osteosarcoma patients was genotyped using the DMET Plus array (containing 1,936 genetic markers in 231 drug metabolism and transporter genes). Associations between genetic variants and EDP were assessed using logistic regression models and associated variants (P<0.05) were validated in independent cohorts of 146 (Spain and UK) and 28 patients (Australia). In the association analyses, EDP was significantly associated with an SLC7A8 locus and was independently validated (meta-analysis validation cohorts: OR 0.19 [0.06-0.55], P=0.002). The functional relevance of the top hits was explored by immunohistochemistry staining and an in vitro transport models. SLC7A8 encodes for the L-type amino acid transporter 2 (LAT2). Transport assays in HEK293 cells overexpressing LAT2 showed that doxorubicin, but not cisplatin and methotrexate, is a substrate for LAT2 (p < 0.0001). Finally, SLC7A8 mRNA expression analysis and LAT2 immunohistochemistry of osteosarcoma tissue showed that the lack of LAT2 expression is a prognostic factor of poor prognosis and reduced overall survival in patients without metastases (p = 0.0099 and p = 0.14, resp.). Conclusions: This study identified a novel locus in SLC7A8 to be associated with EDP in osteosarcoma. Functional studies indicate LAT2-mediates uptake of doxorubicin, which could give new opportunities to personalize treatment of osteosarcoma patients.